2D-PIV Experimental Study on the Air Distribution with Natural Convection Effect of Passengers in an Air Cabin Mockup. (2015) - Zhu, Xueliang; Liu, Junjie; Cao, Xiaodong; Li, Jiayu
Abstract: Many previous studies have mentioned the critical effect of natural convection caused by passengers heat transfer on the air distribution inside the air cabins, but No study focused on it to make a further experimental or numerical analysis. In fact, the air flow field inside the air cabin with narrow interior space and passengers seated intensively is the result of interaction between natural convection from the passengers and forced convection from the supply air diffusers, including the air jet which plays the most essential part on the flow pattern. This study has measured the air flow jet in a 7-row cabin mockup with 2D-PIV (two dimension Particle Image Velocity) measurement system, and to make comparison of the air jet under isothermal and cooling conditions to analyze qualitatively the impact of natural convection inside the cabin mockup, which is to increase the air jet entrainment and weaken the attaching effect which can also enhance the velocity distribution uniformity. With the variety of air flow volume in a reasonable range of design parameters, we measured the different air velocity fields to quantify the effects of natural convection on the air jet. It can be concluded that the air jet decay rate becomes slower with the enhancement of natural convection.